Lateral Control of Functionally Graded Composite Beam under Static Load by using Piezoelectric Layer - Abdolreza*, Toudehdehghan (IOP Publishing, 2020)
Controlling the deflection of a composite cantilever beam under concentrate static force at the free end is investigated. The composite beam is made of ceramic and metal, which gradually change from ceramic to the metal in thickness coordinate. This kind of composite is called Functionally Graded Material (FGM). In FGM, material properties are presumed to differ as an exponential function. The governing equation of the rectangular composite beam is based on Euler-Bernoulli deformation theory. Two control models are considered in this article. First, two piezoelectric actuators are attached to the two sides of the composite beam which each of these actuators is applied the voltage separately. To control the deflection of each point of the composite beam, the difference between the two voltages is considered constant. Second, a piezoelectric actuator is attached to the free end of the composite beam, which also provides a relation to control any desired point of the composite beam. By comparing the two models, the superiority of the second model is proven.